IMPLEMENTATION TREND MOMENT FOR PREDICTING HOYA BREAD SALES - Wahyuni Siregar; Arridah Zikra Syah; Indra Ramadona Harahap Ramadona Harahap (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Prediction of bread sales accurately and efficiently using the trend moment method. A forecast to produce an estimated number of bread supplies in the future, so that there is no excess or shortage of bread stock in the coming month. In this study, data on bread sales are used every month, from January to December 2021. Sales records for each month are useful to see whether they have increased or decreased. The results of this study are the creation of a computerized system that is able to generate approximate numbers in predicting sales for the next month using the PHP and MySQL programming languages, making it easier to find out how much bread will be sold and considering the stock of goods and how much will be produced in the next month. the following month so that there is no shortage or excess of bread stock. The results of sales predictions for 12 months in 2021, produce predictions in January 2022, in the 13th period with MAD (Mean Absolute Deviation) results of 40.08% and MSE (Mean Squared Error) rates of 27.64%.